PENANADA KALA DALAM SEKOLO ADAT DAERAH MELAYU JAMBI - Rustam Rustam (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2017)
Research on Penanada Kala in Seloko Adat Jambi Malay is an oral research or foklor. This study is based on the needs of the Jambi Malay community to understand and implement the forms of time or time usage in oral tradition. The problem of this research is how the use of time or time in seloko adat Jambi Malay area? and what meaning is contained in penguin time or time in seloko adat Jambi Malay Area? The purpose of this study is to describe the shape and meaning of marker kala in seloka adat Jambi Malay area. The data in this study are oral and reinforced data with written data. To analyze the data used descriptive method with data analysis technique is the method of extralingual padan with basic technique Pilih Unsur Penentu (PUP) and advanced technique Hubung Banding Samakan (HBS), Hubung Banding Bedakan (HBB). The significance of the markers in the indigenous customs of Malay Jambi is influenced by the use of the word task or forerunner and different word of the letters. The meaning that arises from the event of speech is influenced also by the timelessness and the shortness of time.